Mitochondrial Homeostasis and Signaling in Parkinson’s Disease - Scorziello, Antonella; Borzacchiello, Domenica; Sisalli, Maria Jose; Di Martino, Rossana; Morelli, Micaela; Feliciello, Antonio (Frontiers in Aging Neuroscience, 2020)
The loss of dopaminergic (DA) neurons in the substantia nigra leads to a progressive, long-term decline of movements and other non-motor symptoms. The symptoms in Parkinson’s disease (PD) patients often appear later in the course of the disease, when most of the functional dopaminergic neurons have been lost. The late onset of the disease, the severity of the illness and its impact on the global health system demand earlier diagnosis and better targeted therapy. Genetic mutations affecting key regulators of neuronal physiology and metabolism have been identified and causally linked to few clinical variants of PD. However, the causes of PD remain largely unknown. Several PD-linked genes have been reported to negatively impact on mitochondrial activity, suggesting that mitochondrial dysfunction is pathogenically relevant for the disease. Compartmentalized PKA signaling at mitochondria by A-Kinase Anchor Proteins (AKAPs) ensures efficient transduction of GPCR signals generated at the cell membrane to the organelles, supporting neuronal activity and survival. In PD neurons, enhancing PKA action at mitochondria by AKAPs reverses oxidative damage and promotes survival. Mitochondrial AKAPs also regulates mitochondrial calcium homeostasis by interacting with the sodium calcium exchanger NCX3. Downregulation of NCX3 levels coupled to increased mitochondrial calcium loading and depolarization of mitochondrial membrane have been observed in mesencephalic neurons of PD animal models. These findings implicate disruption of mitochondrial pathways and calcium homeostasis as relevant factors in promoting selective loss of dopaminergic neurons in PD. Here, we will highlight the relevance of dysfunctional mitochondrial signaling in PD, the molecular mechanisms involved and potential therapeutic approaches to restore mitochondrial activity in damaged neurons.